Femoral fixation pattern in cemented Oxford unicompartmental knee arthroplasty: an experimental cadaver study - Clarius, Michael; Mohr, G.; Jäger, Sebastian; Seeger, Jörn Bengt; Bitsch, Rudi G. (The knee, 2010)
Femoral component loosening is a rare but serious complication in cemented Oxford unicompartmental knee arthroplasty (OUKA). In a cadaver study, OUKA was performed in 24 knees to evaluate the femoral fixation pattern. Due to the geometry of bone and implant, three different zones were identified. Complete cement mantles and good interdigitation were found in the spherical part of the implant (zone 1) and around the peg (zone 3), which implies that these are most important for implant fixation. The posterior plane facet (zone 2) is the weak point of the interface due to incompleteness of the cement mantle and a lack of interdigitation. This study suggests that the cancellous bone in zone 2 and the drill holes in sclerotic bone areas should be filled with cement and pressurised prior to component seating.